Coordination is key: Joint attention and vocalisation in infant siblings of children with Autism Spectrum Disorder. Issue 5 (5th August 2018) - Heymann, Perrine; Northrup, Jessie B.; West, Kelsey L.; Parladé, Meaghan V.; Leezenbaum, Nina B.; Iverson, Jana M.
Abstract: Background: Research indicates that social communicative behaviours develop atypically during the second year in Autism Spectrum Disorder (ASD). This study evaluated whether these behaviours also differed in the extent to which they were coordinated across modalities. Aims: To measure joint attention behaviours (e.g., gaze shifts, gestures), vocalisations and their coordination among a cohort of infants with an older sibling with ASD (heightened risk—HR). Methods & Procedures: This prospective longitudinal study examined 50 HR infants at 14, 18 and 24 months. The Early Social Communication Scales (ESCS)—a structured toy‐play task that assesses infant joint attention behaviour—was administered to infants at each age point in the home. Infants' joint attention behaviours, vocalisations and instances where they overlapped were coded from videos. At 36 months, nine infants received an ASD diagnosis (HR‐ASD), 15 had a significant language delay (HR‐LD) and 26 were classified no diagnosis (HR‐ND). Outcomes & Results: Findings revealed that HR‐ASD infants produced fewer advanced joint attention behaviours, and their vocalisations were less frequent and less advanced than HR‐LD and HR‐ND infants. Notably, HR‐ASD infants also coordinated these behaviours together less frequently than their HR peers. Conclusions & Implications: Differences in the coordination of early communicative behaviours may have negative cascading effects on social and language development for infants who develop ASD. Current intervention practices may be complemented by efforts to increase the coordinated quality of communicative behaviours.